First-year Academic Performance of Pharmacy Students Based on High School Status and Major - Soegiantoro, Didiek Hardiyanto; Soegiantoro, Holy Rhema; Soegiantoro, Gregory Hope (Syntax Literate, 2021)
The purpose of the research is provides a descriptive first-year academic performance of pharmacy students based on high school status and major. This research is a descriptive research with cross-sectional method using all pharmacy students as sample. The results of this research are percentage of pharmacy students from public high schools is 33% and 67% from private high schools. The percentage of specialization majors in high school is 6% pharmacy, 85% science and 9% non-science. The academic performance of students from private high schools is better than that of public high schools. Pharmacy majors in high school produce the highest academic performance, meanwhile, non-science majors show the lowest academic performance, the principal results. Conclusions in this research is first-year academic performance for pharmacy students from private high schools is better than public high schools, as well as pharmacy major in high school showing the highest GPA and non-science major showing the lowest GPA